2022
DOI: 10.3390/rs15010088
|View full text |Cite
|
Sign up to set email alerts
|

STA-GAN: A Spatio-Temporal Attention Generative Adversarial Network for Missing Value Imputation in Satellite Data

Abstract: Satellite data is of high importance for ocean environment monitoring and protection. However, due to the missing values in satellite data, caused by various force majeure factors such as cloud cover, bad weather and sensor failure, the quality of satellite data is reduced greatly, which hinders the applications of satellite data in practice. Therefore, a variety of methods have been proposed to conduct missing data imputation for satellite data to improve its quality. However, these methods cannot well learn … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 51 publications
0
15
0
Order By: Relevance
“…It is labeled as missing value by both log-likelihood ratios (LLR) and Latent Semantic Indexing (LSI), and as analysis ( Some study opportunities that received less attention comprised missing data and the class center method, as initially explored by Nugroho et al [169]- [172], building upon the work initiated by Tsai et al [173]. More recently, the GAN method for data imputation was developed and studied [133], [137], [147], [148], [174]- [200]. To identify emerging areas of research and trends, the CiteSpace algorithm-dependent analytical tool generated keywords burst map from the strongest citation bursts in scientific literature.…”
Section: Figure 17 Co-occurrence Networkmentioning
confidence: 99%
See 1 more Smart Citation
“…It is labeled as missing value by both log-likelihood ratios (LLR) and Latent Semantic Indexing (LSI), and as analysis ( Some study opportunities that received less attention comprised missing data and the class center method, as initially explored by Nugroho et al [169]- [172], building upon the work initiated by Tsai et al [173]. More recently, the GAN method for data imputation was developed and studied [133], [137], [147], [148], [174]- [200]. To identify emerging areas of research and trends, the CiteSpace algorithm-dependent analytical tool generated keywords burst map from the strongest citation bursts in scientific literature.…”
Section: Figure 17 Co-occurrence Networkmentioning
confidence: 99%
“…Centrality served as a metric for gauging a chosen topic's significance, whereas density measured its level of development. These fundamental themes and evolving topics describe crucial facets of the discipline that had not yet reached their full potential, presenting opportunities for further investigation, such as missing data imputation using GAN [133], [137], [147], [148], [174]- [200], and deep learning [10], [205]- [216].…”
Section: Figure 20 Thematic Mapmentioning
confidence: 99%
“…The work of Bernardini [ 15 ] and others is based on generative adversarial networks under clinical conditions, using nonlinear and multivariate information between data to fill missing values, which is more robust than other algorithms. Wang [ 16 ] and others proposed a spatiotemporal attention generative adversarial network algorithm (STA-GAN) to learn short-term correlation and dynamic spatial correlation in satellite data in order to improve the filling effect when the missing data rate is large. Zhang et al [ 17 ] proposed a self-attention generative adversarial network filling model (SA-GAIN) to fill in missing data of traffic flow.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the important advantages of using remote sensing data for monitoring marine Chl-a concentrations, several factors can affect the accuracy and integrity of such data. These include sensor resolution, atmospheric disturbances, tides and waves, reflectance absorption, and so on [14,15]. Researchers have noted that because of the complexity of the marine environment and the inherent limitations of remote sensing techniques, there may be incomplete and sporadic data on Chl-a concentrations, both in terms of spatial and temporal coverage [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…Recent research demonstrates the efficacy of Machine Learning (ML) methodologies as viable alternatives to traditional statistical approaches in the realm of spatiotemporal imputation [14][15][16]20,21]. He Qian compared the interpolation of Chinese temperature data based on three machine learning methods (random forest, support vector machine, and Gaussian process regression) and three traditional interpolation methods (inverse distance weighting, ordinary kriging, and ANUSPLIN), and found that the machine learning algorithms performed better at interpolating temperature prediction compared to the traditional algorithms [22].…”
Section: Introductionmentioning
confidence: 99%